Ureteric Trauma following Stent Removal in Kidney Transplant Recipient: A Unique Case of Prolonged Morbidity - Ahmad Mirza; Imran Gani; Andy Shi Huang; Ravi Mallavarapu; Laura Mulloy; Muhammad Saeed; Rajan Kapoor (Case Reports in Transplantation)
A 52-year-old African-American male patient with end-stage renal disease due to hypertension underwent deceased donor kidney transplant procedure with no immediate complications. The postprocedure complications, interventions, and course were abstracted by chart review. The ureteric stent was removed with flexible cystoscopy on postoperative day (POD) 24. 24 hours later, the patient presented with abdominal pain and inability to urinate. An urgent ultrasound and noncontrast CT scan showed grade 4 hydronephrosis of the transplanted kidney. A percutaneous nephrostomy stent was placed for urinary diversion. A large ureteric hematoma filling the lumen of the mid to distal ureter was identified on the nephrostogram and was evacuated. A follow-up nephrostogram on POD 44 revealed a distal ureter stricture and persistent well-formed midureter filling defect. A repeat nephrostogram performed at POD 72 was done with stricture dilatation, internalization of stents, and removal of a percutaneous nephrostomy tube. The patient was maintained on antibiotics for UTI prophylaxis throughout the course.